Essential immune functions of fibroblasts in innate host defense - Cavagnero, Kellen J.; Gallo, Richard L. (Frontiers in Immunology, 2022)
The term fibroblast has been used generally to describe spindle-shaped stromal cells of mesenchymal origin that produce extracellular matrix, establish tissue structure, and form scar. Current evidence has found that cells with this morphology are highly heterogeneous with some fibroblastic cells actively participating in both innate and adaptive immune defense. Detailed analysis of barrier tissues such as skin, gut, and lung now show that some fibroblasts directly sense pathogens and other danger signals to elicit host defense functions including antimicrobial activity, leukocyte recruitment, and production of cytokines and lipid mediators relevant to inflammation and immunosuppression. This review will synthesize current literature focused on the immune acting fibroblasts at barrier tissues to highlight the previously unappreciated importance of these cells in host defense.